Start Now to Design Citrus Groves for Mechanical Harvesting - Bob Rouse; Steve Futch (EDIS)
Change has kept the Florida citrus industry competitive during the last century. The Florida citrus industry is now facing one of its greatest challenges -- the change to mechanical harvesting or lose competitiveness in the global juice market. It is a general consensus among industry leaders that efficiencies in harvesting offer the greatest potential to reduce costs and keep our juice industry economically viable. Other tree crops (tart and sweet cherry, pistachios, prunes, olives) that would have been lost, have moved to mechanical harvesting to survive, but a generation of change was required and thinking had to be adjusted in lines with a commodity. This document is HS974, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2004.